2010
DOI: 10.1080/19440040903493785
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of wild boar meat and relationship between age and bioaccumulation of heavy metals in muscle and liver tissue

Abstract: This study determined the accumulation of selected heavy metals (Pb, Cd, Hg and As) in tissues of wild boar. The tested animals were divided into three age groups, which allowed analysis of the statistical/mathematical relationship between their age and contamination of their tissues. For determination of heavy metal content, samples were taken from the longissimus muscle of the back and from the tail lobe of the liver. It has been stated that, in wild boar, accumulation of lead and cadmium in muscle and liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 25 publications
1
8
1
Order By: Relevance
“…However, all of the liver samples analyzed had cadmium levels lower than the MRL set for pig offal: 0.5 mg kg -1 ww. Our data on cadmium occurrence in WB meat fell within the range of published data, i.e., between 0.001 and 0.355 mg kg -1 ww (Medvedev 1999;Rudy 2010;Taggart et al 2011). Compared with the data presented by Hernández et al (1985) regarding wild Spanish fauna, we observed lower levels of cadmium contamination in WB meat (geometric means of 0.07 vs. 0.12 mg kg -1 ww) as well as WB liver (geometric means of 0.067 vs. 0.45 mg kg -1 ww).…”
Section: /2006 For Pigs and Other Farmed Species (European Commissupporting
confidence: 86%
“…However, all of the liver samples analyzed had cadmium levels lower than the MRL set for pig offal: 0.5 mg kg -1 ww. Our data on cadmium occurrence in WB meat fell within the range of published data, i.e., between 0.001 and 0.355 mg kg -1 ww (Medvedev 1999;Rudy 2010;Taggart et al 2011). Compared with the data presented by Hernández et al (1985) regarding wild Spanish fauna, we observed lower levels of cadmium contamination in WB meat (geometric means of 0.07 vs. 0.12 mg kg -1 ww) as well as WB liver (geometric means of 0.067 vs. 0.45 mg kg -1 ww).…”
Section: /2006 For Pigs and Other Farmed Species (European Commissupporting
confidence: 86%
“…A similar value was recorded for the renal tissue for which, even for the MTI harvesting area, the levels of accumulation were significantly higher than those observed in the other areas (P<0.05) ( Figure 2). There was no difference between data collected on the presence of cadmium in wild boar muscle in the present paper and those values reported in the literature (range 0.001-0.355 mg Cd kg -1 w.w.) (Rudy, 2010;Taggart et al, 2011). Nevertheless, we observed lower values than those reported by Hernández et al (1985) for cadmium in muscle (geometric means of 0.07 vs 0.12 mg Cd kg -1 w.w.) or in liver (geometric means of 0.067 vs 0.45 mg Cd kg -1 w.w.).…”
Section: Cadmiumcontrasting
confidence: 84%
“…An almost 1.5 times lower Pb content in the livers of wild boar was found by Rudy (2010) in that region of Poland (lubelskie and podkarpackie voivodeships). However, this author observed an increase of lead content in the described area from 2002 to 2006.…”
Section: Discussionmentioning
confidence: 93%
“…Game animals are considered good indicators of environment contamination, as they remain in natural habitats all life long, and accordingly, it influences their health status (Skibniewski et al 2015;Wieczorek-Dąbrowska et al 2013;Bilandžic et al 2012;Garcia et al 2011;Rudy 2010;Bilandžic et al 2010;Kalisińska et al 2003;Kucharczak et al 2003;Szkoda and Żmudzki 2001;Pokorny 2000;Żarski et al 1994;Michalska and Żmudzki 1992).…”
Section: Introductionmentioning
confidence: 96%